2020
DOI: 10.3390/su12104054
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry Heritage Systems as Agrobiodiversity Hotspots. The Case of the Mountain Oases of Tunisia

Abstract: Traditional agricultural systems are receiving increasing attention at the international level due to their multifunctional role. The Globally Important Agricultural Heritage Systems (GIAHS) programme of the Food and Agriculture Organization (FAO) aims to identify agricultural systems of global importance, preserve landscape, agrobiodiversity and traditional knowledge and apply the principles of dynamic conservation to promote sustainable development. Biodiversity associated to traditional agricultural practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Mankind has largely modified the surrounding environment taking advantage of its potentialities in order to fulfil his needs. Undoubtedly the human actions in modifying the natural features have contributed to shape unique landscapes which are an example of human and nature coevolution during the centuries according to local traditions and cultural values (Santoro et al 2020). In many arid countries, runoff water-harvesting systems support the livelihood of the rural population and Southeast Tunisia provides a typical example of the intensive management of scarce water resources in southern Mediterranean drylands (Ouessar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mankind has largely modified the surrounding environment taking advantage of its potentialities in order to fulfil his needs. Undoubtedly the human actions in modifying the natural features have contributed to shape unique landscapes which are an example of human and nature coevolution during the centuries according to local traditions and cultural values (Santoro et al 2020). In many arid countries, runoff water-harvesting systems support the livelihood of the rural population and Southeast Tunisia provides a typical example of the intensive management of scarce water resources in southern Mediterranean drylands (Ouessar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is beneficial as an investment in the mid to long term for the local communities, also because it takes into account the sustainable development goals as defined by the United Nations. Analogously to the Qingtian Rice-Fish Co-culture system, the successful GIAHS cases in the world have had similar situations by raising prices of distinctive agricultural products to drive local economic development, rural community construction, and cultural inheritance, such as Sado's Satoyama in Harmony with Japanese Crested Ibis in Japan [16], the agriculture system in Chiloé Island of Chile [17,18], the agroforestry heritage systems in the mountain oases of Tunisia [19], and the traditional terraced landscapes in Chianti of Italy [20].…”
Section: Introductionmentioning
confidence: 99%
“…These are systems in which the social and ecological dynamics involve multiple interactions between human and natural components in continuous evolution. Traditional oases, as mentioned by Santoro et al [35], can be considered as agroforestry systems, as reported by the FAO on the basis of ICRAF (International Centre for Research in Agroforestry), and represent an important reservoir of genetic and cultural biodiversity that must be safeguarded for future generations. In fact, it is important to underline how the local genetic heritage, with its diversity and adaptability developed over time, can represent a sort of mitigation against climate change in areas with high fragility and complexity, as an alternative to new irrigation perimeters (monoculture of date palms) based on rational agronomic planning that create high competition for the use of the limiting resource, i.e., water [36].…”
Section: Introductionmentioning
confidence: 99%